Pengaruh Kompensasi, Lingkungan Kerja Dan Komitmen Organisasi Terhadap Kepuasan Kerja Dan Stres Kerja Menjadi Variabel Intervening Pada Pt. Ekosjaya Abadi Lestari - Syayidati Mauliah; Lilik Indayani (International Journal on Orange Technologies, 2021)
This study aims to determine the effect of compensation, work environment and organizational commitment to job satisfaction and job stress as intervening variables at PT. Ekosjaya Abadi Lestari.This research is a quantitative research with hypothesis testing. The sample used in this study were 104 employees at PT. Ekosjaya Abadi Lestari. The analytical tool used in this research is path analysis using a questionnaire program whose measurements use a Likert scale which is tested for validity and reliability.The results of this study prove that compensation has a significant effect on job stress, work environment has a significant effect on job stress, organizational commitment has a significant effect on job stress, compensation has a significant effect on job satisfaction, work environment has a significant effect on job satisfaction, organizational commitment has a significant effect on job satisfaction. , Job stress has a significant effect on job satisfaction, There is no indirect effect of compensation on employee job satisfaction through job stress as an intervening variable, There is no indirect effect of work environment on employee job satisfaction through job stress as an intervening variable, There is no indirect effect of commitment organization on employee job satisfaction through job stress as an intervening variable.